Flame Retardants Polymer Blends, Composites and Nanocomposites - Visakh, P. M.; Arao, Yoshihiko (Engineering Materials, 2015)
This book summarizes comprehensively many recent technical research accomplishments in the area of flame retardant research. It presents mainly flame retardant studies of polymer blends, composites and nanocomposites such as rubber, thermosets and thermoplastics. This book discusses different types of flame retardant using in polymers especially nanocomposites, as well as the role and chemistry. Leading researchers from industry, academy, government and private research institutions across the globe contribute to this book. Academics, researchers, scientists, engineers and students in research and development will benefit from an application-oriented book that helps them to find solutions to both fundamental and applied problems.